1994
DOI: 10.1111/j.1552-6909.1994.tb01850.x
|View full text |Cite
|
Sign up to set email alerts
|

Major Concerns of Women After Cesarean Delivery

Abstract: Objective-To identify women's major physiologic, psychologic, and life-style concerns at 2 and 8 weeks after cesarean delivery. Design-Descriptive study with open-ended interviews.Setting-Large urban hospital affiliated with a major university.Participants-One hundred six women who had unplanned cesarean deliveries and delivered live, full-term neonates.The mean maternal age was 28.7 years.Main Outcome Measures-The major physiologic, psychologic, and life-style concerns.Results-Seven women reported no concerns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…At six weeks postpartum, women continued to report positive adaptation responses, including relatively high self-esteem, nearly full functional status, positive feelings about the baby, and positive changes in marital relationship quality. Miovech et al (1994) identified physiologic concerns at two weeks postpartum, including pain, incision problems, activity intolerance, fatigue, gastrointestinal disturbances and breast and nipple problems, which decreased by eight weeks postpartum. The women also reported psychological concerns about changes in activity, mood, family interactions, body image, child care arrangements, healing, fatigue, finances and work or school, which diminished slightly between 2-8 weeks postpartum.…”
Section: Adaptation To Caesarean Birthmentioning
confidence: 99%
See 2 more Smart Citations
“…At six weeks postpartum, women continued to report positive adaptation responses, including relatively high self-esteem, nearly full functional status, positive feelings about the baby, and positive changes in marital relationship quality. Miovech et al (1994) identified physiologic concerns at two weeks postpartum, including pain, incision problems, activity intolerance, fatigue, gastrointestinal disturbances and breast and nipple problems, which decreased by eight weeks postpartum. The women also reported psychological concerns about changes in activity, mood, family interactions, body image, child care arrangements, healing, fatigue, finances and work or school, which diminished slightly between 2-8 weeks postpartum.…”
Section: Adaptation To Caesarean Birthmentioning
confidence: 99%
“…The focus of nursing interventions in the postpartum period should be maintenance and promotion of care continuity, access to teaching and counselling and monitoring for early detection and treatment for problems (Brooten 1995). Research-based recommendations for nursing interventions to improve responses to caesarean birth include comprehensive antenatal preparation (Fawcett & Burritt 1985), changes in hospital policies to support partner participation and sustained contact with the neonate (Reichert et al 1993) and discharge planning, education and extended home follow-up through the first 2-3 months postpartum (Miovech et al 1994). Burns-Vandenburg and Jones (1999) retrospectively examined nursing interventions identified by student nurses during postpartum home visits, using the Omaha System Intervention Scheme.…”
Section: Interventions For Caesarean-delivered Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Seventeen percent reported difficulties with normal activities such as getting out of bed, walking, bending, lifting, and tending the infant at 2 weeks, and 9% continued to experience problems at 8 weeks. • 1% to 6% required a transfusion.…”
Section: Maternal Mortality and Short-term Morbiditymentioning
confidence: 99%
“…Distress and depression after caesarean section are common, even when a woman has consented to, or even welcomed, the surgery 1 2 3 4. It is painful to contemplate what an enforced caesarean section would be like, particularly for a woman with paranoid schizophrenia.…”
Section: Commentarymentioning
confidence: 99%